Quantum Revolution: Integrating Nanotechnology, Artificial Intelligence and Sustainable Innovations for the Future - Pant, Alka; Kothiyal, Ashutosh; Rawat , Vandana (International Journal of Basic and Applied Sciences, 2025)
“Every End Marks a New Beginning,” Cycle Continues—Life Changes! The world takes a step forward towards the future. The future is where revolutionary technology takes place and exploits quantum mechanics principles like superposition, entanglement, and interference. By existing in multiple states simultaneously, qubits perform fast and optimize operations growth. This paper explores the use case of quantum computing’s potential and integration with cutting-edge fields such as nanotechnology, AI, advanced DNA data storage, and sustainable Li-S energy storage devices. Achieving quantum computer integration with nanotechnology, advancing hardware for future challenges, and space exploration’ missions by precisely engineering qubit materials, superconducting circuits, and quantum dots. Graphene, carbon nanotubes, and fabrication techniques for driving scalable quantum device production. Quantum machine learning (QML) algorithms to solve complex optimizations and predictive tasks. Researching optimal solutions in data and battery storage systems and finding the best algorithm in quantum networking and communication for long-range connectivity with a fast and secure network. Investigating challenges such as error corrections, cost, accessibility, and adaptability. Combining all modern innovations with one technology offers the best result that can change the theoretical fiction world into the real world, not today, but in a few decades.
Keywords: Quantum computing, Nanotechnology, Artificial intelligence, Machine learning, Sustainable Li-S batteries